IMPLEMENTATION OF PEDAGOGICAL ETHICS IN FUTURE TEACHERS - Kamolova, Shirin (Журнал Педагогики и психологии в современном образовании, 2022)
This article discusses the formation of the pedagogical behavior of future teachers. There are examples of teachers’ ethics.